Students' Creativity in Solving Mathematical Problems of Reflection Material in The Context of Songket Palembang - Ifana, Bernika Indrialis; Zulkardi, Zulkardi; Susanti, Ely (Al-Khawarizmi, 2023)
Creativity in mathematics is one of the abilities that students in solving a problem must master. With creativity, students can develop their ideas to produce various solutions. However, in reality, the ability to think creatively is still low. This is because teacher-centred learning does not provide opportunities for students to develop their ideas creatively. Therefore, this study aims to describe the emergence of indicators of students' creative thinking abilities in solving mathematical problems on reflection material using the Palembang songket context. This type of research is a qualitative descriptive research subject, namely 3 class IX students. The research was carried out in three stages, namely, the preparation stage, the implementation stage, and the data analysis stage. The data in this study were collected through written tests and interviews. A written test was conducted to measure students' creative thinking skills data reduction, data presentation, and conclusion will be analyzed in three stages. The study found that fluency, flexibility, and elaboration were the most commonly used indicators of students' creative thinking abilities. Meanwhile, for the authenticity indicator, only one subject melts the indicator.Keywords:  Student Creativity, Reflection Material, Context